Divalproex sodium regulates ataxin-3 translocation likely by an importin α1-dependent pathway. Issue 11 (7th August 2019) - Wang, Zijian; He, Fengqin; Abeditashi, Mahkameh; Schmidt, Thorsten
Abstract : Nuclear localization of ataxin-3 plays a fundamental role in seeding aggregation and the pathology of spinocerebellar ataxia type 3 (SCA3). However, very few compounds that are able to modulate the nuclear transport of ataxin-3 have been identified. In our previous study, we found that divalproex sodium (DVS) reduced heat shock-induced nuclear localization of ataxin-3. However, the mechanism of DVS in the translocation of ataxin-3 still remains unknown. There is accumulating evidence that importins are regulated by acetylation, and histone deacetylase inhibitors can interrupt this process. With this in mind, we used cells coexpressing ataxin-3 and importin α1 (encoded by KNPA2) to probe whether ataxin-3 is the shuttling cargo of importins and whether DVS plays a role in the nuclear transport of ataxin-3 through the transport protein pathway. Here, we reported that importin α1 enhanced nuclear amount of ataxin-3 and increased the aggregate formation and that DVS restored it to the normal level. Importantly, ataxin-3 is shown to directly bind to importin α1. Moreover, DVS modulated the function of importin α1 likely by altering its localization. We believe that this study provides a proof of principle for addressing the mechanism of DVS and furthers our understanding of the role of importins in the nuclear accumulation of ataxin-3 in SCA3. Abstract : Supplemental Digital Content is available in the text.